The Tropical Agriculturalist series 3 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Tropical Agriculturalist seriesLivestock product/on systems examines how individual species of domestic livestock can be integrated into the whole concept of sustainable agriculture in the tropics. The main part of the book is devoted to a...